Նիկողայոս Մառի դերը հայագիտության բնագավառում - Մկրտչյան, Դոնարա
In the article shows that Nikolai Yakovlevich Marr was an outstanding scientist, one of the brightest stars in the constellation of Russian Orientalists of the end XIX and early XX centuries. Unfolding a very comprehensive research activities in the field of armenology, Marr raised to a new level Russian Caucasus Studies. Stressing the unity of ways of development of the Caucasian peoples and considered the Caucasus as a single cultural world, Marr was a champion of both solidarity and friendship between the peoples of the Caucasus. Marr was highly knowledgeable and versatile scholar, and not only a philologist, a linguist and philologist - but equally historian, archaeologist and historian of culture. He repeatedly pointed to the need for a multilateral comprehensive study of monuments of material and spiritual culture, which were the result of the creativity of the people living in a particular historical, cultural and social environment, not in isolation, but in close contact with neighboring peoples. В статье показывается, что Николай Яковлевич Марр был незаурядным ученым, одним из наиболее ярких звезд в созвездии русских востоковедов конца XIX и первой трети XX вв. Развернув весьма обширную научную деятельность в области арменоведения, Н. Я. Марр поднял на новую ступень русское кавказоведение. Подчеркнув единство путей развития кавказских народов и рассмотрев Кавказ как единый культурный мир, Н. Я. Марр одновременно был поборником солидарности и дружбы между кавказскими народами. Н. Я. Марр был высоко эрудированным и многогранным ученым — не только лингвистом и филологом,— но и в равной мере историком, археологом и историком культуры. Он неоднократно указывал на необходимость многостороннего комплексного изучения памятников материальной и духовной культуры, явившихся результатом творчества данного народа, проживавшего в определенной культурно-исторической и социальной среде, не в отрыве, а в тесном контакте с соседними народами.
Keywords: Հայագիտություն